AB1158 Efficacy and security of anakinra treatment in patients with systemic-onset juvenil idiopathic arthritis: "Initial results from a register of two pediatric reumatologic units from spain". (23rd January 2014) - Calvo, I.; Marvillet, I.; Lόpez, B.; Marco, A.; Rodriguez, Y.; Bou, R.; Ricart, S.; Calzada, J.; Torrent, V.; Antόn, J.
Abstract : Background: Interleukin-1 (Il-1) is a critical cytokine for the pathogenesis of systemic JIA. Treatment with anakinra (Il-1 receptor antagonist) has been reported to be effective in some patients with systemic-onset juvenile idiopathic arthritis (SoJIA). Objectives: To examine the safety and the efficacy of anakinra treatment in a cohort of SoJIA patients regarding clinical and biological data from two reference centers. Methods: We retrospectively reviewed the medical records of 50 patients with SoJIA, treated with anakinra (1-3 mg/kg/day) at the pediatric rheumatologic units of two tertiary university hospitals in Spain between 2004 and 2011. Anakinra's effects were studied on several parameters including clinical parameters (fever, rash, limited and active joints), time since symptoms started and diagnose to beginning of treatment, biological parameters (erythrocyte sedimentation rate (ESR), C-reactive protein levels (CRP), ferritin, and white blood cell count (WCC)). Resulting data were analysed to characterize therapies, clinical course and adverse events. Statistics were obtained using SPSS program. Results: There were 28 (56%) boys and 22 (44%) girls. Age at diagnosis varied from 7 months to 15, 8 years (median 6, 6 years). Time from diagnosis to anakinra treatment varied from 0 to 118 months (median 16, 43 months). Treatment duration varied from 0 to 70 months (mean 23, 6 months). Statistical significance was found when comparing at 0 and 6 month of treatment with anakinra in: Fever (p<0, 001), rash (p<0, 001), ESR (p<0, 001), CRP (p<0, 001), Ferritin (p<0, 049), WCC (p<0, 001), active arthritis joint count (p<0, 001), limited joint count (p<0, 031). A significant relationship (Spearman correlation) was observed regarding the number of active and limited joints when we analysed the time passed between diagnosis and anakinra treatment onset (Table 1 ). Side effects at 6 months were hipertransaminasemia (1 patient), macrophage activation syndrome (1 patients), tipe I hypersensibility (2 patients). Pain at the anakinra injection site was present in 70% of the patients but in all cases, pain disappeared within 2 months. Conclusions: These results show that shortening the time passed from diagnosis to anakinra treatment reduces the number of active and limited joints, since then, anakinra should be considered as a first line therapy in SoJIA patients. Disclosure of Interest: None Declared